Marie Tremaine, 1902-1984 - Corley, Nora T. (ARCTIC, 1985)
One of the first important projects embarked upon by the nascent Arctic Institute of North America in 1949 was a bibliography of literature concerning the arctic regions of the world. As project director and editor of the Arctic Bibliography Project the Institute chose Marie Tremaine, at that time and until her death last summer Canada's foremost bibliographer. Born in Buffalo, New York, in 1902 to Canadian-born parents, Marie Tremaine came to Canada in 1911. She was educated at the Humberside College Institute in Toronto and Victoria College of the University of Toronto, where she honoured in English and history, attaining her Bachelor of Arts in 1926. The following year Marie Tremaine joined the Reference Division of the Toronto Public Library. In 1929, having won the first Canadian fellowship for study abroad awarded by the Carnegie Corporation, Marie Tremaine attended the University of London School of Librarianship . On her return to the Toronto Public Library, Marie Tremaine became involved in the library's contribution to the centennial of the city of Toronto: the listing of the library's significant collection of Canadiana. . This important bibliography authority, containing 4646 titles (8286 if the supplement is included), is used extensively by librarians, booksellers and others interested in early works on Canada. In 1935 Marie Tremaine was awarded a second Carnegie fellowship. For two years she attended Yale University, carrying on research into early Canadian bibliography and beginning her comprehensive bibliography of works published in Canada before 1800 . In 1941 Marie Tremaine was appointed associate head of the Reference Department of the Toronto Public Library. Then in 1947, the Arctic Bibliography Directing Committee . approached Marie Tremaine to take on the new position of project director of the Bibliography Project, the object of which was to prepare an annotated bibliography of material published dealing with the arctic regions, covering all subject fields and languages. . In all, Marie ...